PENINGKATAN KETERAMPILAN MENULIS TEKS BERITA DENGAN MODEL KOOPERATIF JIGSAW PADA SISWAKELAS VIII-B SMP NEGERI 1 PANCURBATU - Ester Hutasoit; Petrus Purwanto; Ermina Waruw (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
The ability in writing news text is a competence that must be achieved in KD 4.2 that present information data in the form of oral and written news considering the structure, elements and language. The purpose of the study is to improve news text writing skills by using the cooperative jigsaw model for students in class VIII-B of Pancurbatu 1 Public Middle School. Research method used is Classroom Action Research (CAR). Based on the results of class action research that has been carried out in 2 cycles, it can be seen from the activities of students in the learning process that their achievement was increasing in each cycle. In the first cycle the completeness of the test is 42,3%. In cycle II it has increased, namely classical completeness as many as 84,61%. So, it can be concluded that the increase in classical completeness is 42.31%. Based on the results of class action research, using the two cycles with the cooperative jigsaw model, can improve news writing skills for students of class VIII-B of SMP Negeri 1 Pancurbatu Academic Year 2018/2019